PERCERAIAN DAN PERNIKAHAN DINI DI KABUPATEN SEMARANG - Nizar, Muchamad Coirun; Ghofar Shidiq (Indonesian Association of Islamic Family Law Lecturers, 2019)
The obscurity of the ideal age for a marriage in classical fiqh reference requires the existence of ijtihad among contemporary jurists to determine the ideal age limit for a marriage. The result of the ijtihad is the formulation of a Compilation of Islamic Law which among one of the articles discusses the minimum limit for someone who will hold a marriage (article 15 KHI) which is 21 years. Including the phenomenon that is rife in Indonesia is the rise of early marriage. Early marriage is defined as a marriage that takes place before maturity is reached both physically and psychologically. In an ideal setting, a marriage continues until death approaches one married couple as exemplified by Rasulullah SAW. But now, divorce occurs in many areas. Divorce occurs because of conflict between husband and wife, or the lack of compatibility between both husband and wife to continue the household. This article is the result of a research linking the occurrence of early marriage and divorce rates in Semarang. The object of this research is the decisions in PA Ambarawa ruling relating to divorce and marriage dispensation requests. In the end, the rise of cases of early marriage in Semarang Regency is due to the rise of free association between teenagers. The results of this study concluded that some divorce decisions in PA Ambarawa in 2014 occurred against the background of early marriage.